Treatment of Multiple Primary Malignancies With PD-1 Inhibitor Camrelizumab: A Case Report and Brief Literature Review - Wan, Yuchen; Wang, Zhixue; Yang, Ning; Liu, Fenye (Frontiers in Oncology, 2022)
Background: With significant advance in the diagnostic tools and treatment modalities of cancer, the incidence of multiple primary malignancies (MPMs) has increased in the last decades. The therapeutic option changed with the arising of immune checkpoint inhibitors (ICIs), which have improved the survival of a broad spectrum of tumors. However, little information is available when it comes to the efficacy, resistance, and underlying mechanisms of ICIs. Case presentation: A 67-year-old woman was diagnosed with pulmonary sarcomatoid carcinoma (PSC) with a history of hepatocellular carcinoma (HCC) and viral hepatitis B. Following the lack of response to systemic chemotherapy, she was treated with camrelizumab, an anti-PD-1 monoclonal antibody, in combination with chemotherapy, and obtained a partial response (PR) both in PSC and HCC. After a course of nine-month treatment, the PSC lesion shrank still, while HCC was evaluated as progressive disease (PD) with an increased diameter of liver neoplasm, elevated alpha-fetoprotein (AFP) and enlarged abdominal lymph nodes. Then, with the addition of radiotherapy for abdominal metastasis, the lung lesion was continuously shrinking, in the meantime, the liver neoplasm and abdominal lymph nodes showed no significant enlargement. Conclusion: Camrelizumab combination therapy could consistently benefit the MPMs patient with PSC and HCC, which may be a promising option for patients with MPMs.